QUALITY FUNCTION DEPLOYMENT FOR QUALITY PERFORMANCE ANALYSIS IN INDONESIAN AUTOMOTIVE COMPANY FOR ENGINE MANUFACTURING - Jaqin, Choesnul; Rozak, Ahmad; Purba, Humiras Hardi (ComTech: Computer, Mathematics and Engineering Applications, 2020)
The research aimed to improve the quality problem from the previous plant that contributed to the Rate of Quality (RQ) and Overall Equipment Effectiveness (OEE) value in Cylinder Block Machining (CBM). The research was done in one of an automotive company in Indonesia. It had been applying Total Productive Maintenance (TPM) with Kaizen spirit to make continuous improvement even though this company had reached a world-class level on the Japan Institute of Plant Maintenance (JIPM) standard. To express the needs and wants of the current machining plant and improve quality problems from the previous process in the casting plant, the researchers used Quality Function Deployment (QFD) method. From the result, it is known that shrinkage defect at a casting product becomes the priority of the kaizen team to achieve next process customer satisfaction in a machining plant to increase the RQ and OEE value. By implementing improvement based on the highest value of Technical Priorities (TP) from House of Quality (HOQ), it can increase RQ value in CBM from 96,4% in December 2018 to 97,9% in February 2019. Then, OEE value increases from 92% to 93% within two months.